1999
DOI: 10.1023/a:1021392931450
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study examined the relationship between ritualistic, compulsive-like behaviors and normative fears and phobias in 61 children ranging from 1 to 7 years of age. Parents reported on their children's ritualistic habits, and perfectionistic behaviors that reflect what we have previously called "compulsive-like" behaviors. Parents also reported on their children's fears and phobias. Results indicated that various aspects of children's ritualistic and compulsive-like behaviors are correlated with children's fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 12 publications
2
21
1
1
Order By: Relevance
“…Consistent with our predictions and previous literature [3, 10, 14, 25, 29, 34, 35], our study indicates that IS is positively associated with anxiety and that higher levels of anxiety and IS are both associated with lower levels of EC. Furthermore, our mediation analyses showed that the association between EC and anxiety was mediated by IS and that, in turn, the relationship between IS behaviours and anxiety was mediated by EC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our predictions and previous literature [3, 10, 14, 25, 29, 34, 35], our study indicates that IS is positively associated with anxiety and that higher levels of anxiety and IS are both associated with lower levels of EC. Furthermore, our mediation analyses showed that the association between EC and anxiety was mediated by IS and that, in turn, the relationship between IS behaviours and anxiety was mediated by EC.…”
Section: Discussionsupporting
confidence: 93%
“…During the early development of most children, IS behaviours and typical fears and anxiety, such as fear of strangers, as well as cognitively more complex and anticipatory fears tend to follow a similar developmental trajectory [2, 4, 710]. Furthermore, normative IS behaviours are likely to occur at times of transition, such as bedtime or mealtime, and are often accompanied by typical fears/anxieties, including fear of the dark or separation anxiety [3]. These observations have led to the suggestion that IS behaviours act as an early form of self-regulation, serving to control or constrain the environment thus limiting unpredictability and reducing ensuing fears and anxiety, eventually reducing as more advanced forms of self-regulation develop [5, 11–14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood worries reported by parents increased significantly from 7 years of age and for these older age groups there were consistent relationships between ratings of frequency of worries and intensity and number of RBRI. These results confirmed previous suggestions that one of the functions of RBRI may be to reduce anxiety [20,21,22,23]. …”
Section: Methodssupporting
confidence: 91%
“…The present study is focused on very young children, whose experience of psychological trauma may be different than what adults or older children experience as traumatic because they have different cognitive (Evans et al 1999) and emotion processing (Bell and Wolfe 2004) capacities. Young children also have rapidly developing brains that are potentially vulnerable to long-term structural (Carrion et al 2001;De Bellis et al 2002;Driessen et al 2000) and functional (Perry 2000) impairment as a result of exposure to psychological trauma or PTSD.…”
mentioning
confidence: 99%